Correlation Between Troponin I Levels and Electrolytes of Sodium and Potassium in Acute Coronary Syndrome Patients at Budhi Asih Hospital - Tri Prasetyorini; Diah Lestari; Dzakiyah Ghina Farhah; Suratun; Yudhia Fratidhina (GoAcademica Research & Publishing, 2022)
Acute Coronary Syndrome (ACS) is one of the clinical manifestations of coronary heart disease that most often causes of death. A sensitive laboratory examination to assess the presence of signs of myocardial infarction such as troponin I is used to diagnose ACS. Electrolyte levels can also be impaired in myocardial infarction. Electrolyte imbalance in the blood can affect the conduction and contractility of the heart, especially sodium and potassium which are needed to produce activation of the heart muscle. The aim of this study was to determine the correlation between troponin I levels and sodium and potassium levels of serum in acute coronary syndrome patients with diabetes mellitus. The research design was used a cross sectional analytical observation with secondary data. This study was used the Spearman correlation test with an alpha value of 0.05. The data were taken from the medical records section of Budhi Asih Hospital. The samples were used 65 data of patients. The results showed that there was a correlation between troponin I levels and sodium with a p value 0.001 (p < 0.05), getting a fairly strong closeness level (r = -0.390) and negative direction. Likewise, the levels of troponin I with potassium showed a p value 0.000 (p < 0.05), getting a fairly strong level of closeness (r = -0.487) and a negative direction. From this study, it can be concluded that there was a relationship between troponin I levels with sodium and potassium with a negative correlation direction which indicates that the higher troponin I levels, so the lower the sodium and potassium levels. Electrolyte examination, especially sodium and potassium, is important to help diagnose acute coronary syndrome in knowing the balance of body fluids so as to prevent death.